Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy - Krsmanović Željko; Dinčić Evica; Kostić Smiljana; Lačković Vesna; Bajčetić Miloš; Lačković Maja; Bošković Željko; Raičević Ranko (Vojnosanitetski Pregled)
Introduction. Fast and precise diagnostics of the disease from the large group of adult leukoencephalopathy is difficult but responsible job, because the outcome of the disease is very often determined by its name. Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is caused by the mutation of Notch 3 gene on chromosome locus 19p13. Beside the brain arterioles being the main disease targets, extracerebral small blood vessels are affected by the pathological process. Clinically present signs are recurrent ischemic strokes and vascular dementia. CADASIL in its progressive form shows a distinctive pattern of pathological changes on MRI of endocranium. The diagnosis is confirmed by the presence of granular osmiophilic material (GOM) in histopathological skin biopsies. Case reports. Two young adult patients manifested ischemic strokes of unknown etiology, cognitive deterioration, migraine and psychopathological phenomenology. MRI of endocranium pointed on CADASIL. Ultrastructural examination of skin biopsy proved the presence of GOM in the basal lamina and near smooth muscle cells of arteriole dermis leading to CADASIL diagnosis. The presence of GOM in histopathological preparation is 100% specific for CADASIL. The patients were not searched for mutation in Notch 3 gene on chromosome 19, because some other leukoencephalopathy was disregarded. Conclusion. Suggestive clinical picture, distinctive finding of endocranium MRI, the presence of GOM by ultrastructural examination of histopathological skin biopsies are sufficient to confirm CADASIL diagnosis.